Feeding Concentrate and Market Waste on the Performance of Collared Crickets (Gryllus bimaculatus) - S. Ginting; M Tafsin; A Sadeli; E Sulistyowati (Talenta Publisher, 2024)
In Indonesia, crickets (Gryllus sp.) are used as feed for pet animals, especially insectivorous animals, one of which is the kalung/collared cricket. Collared crickets have a short life cycle, high egg hatchability, fast growth, low feed conversion, and have softer body skin that is preferred by birds and other insectivorous animals. Feed is very important in intensive cricket rearing, especially in hatching crickets. The feed given to crickets is generally in the form of concentrates and leaves. This study aims to determine the effect of giving concentrates and market waste (kale, cabbage, cassava leaves) on the performance of collared crickets (Gryllus bimaculatus). This research was conducted at the Livestock Biology Laboratory, Department of Animal Science, Faculty of Agriculture, Universitas Sumatera Utara, from March to April 2020. This research was conducted experimentally using a completely randomised design (CRD) consisting of 4 treatments and 5 replications. The treatments consisted of P0 = 100% market waste, P1 = 75% market waste + 25% concentrate, P2 = 50% market waste + 50% concentrate, P3 = 25% market waste + 75% concentrate. The results of this study showed that the provision of concentrate and market waste (kale, cabbage, and cassava leaves) had no significant effect on the performance of collared crickets. The average mortality in this study was 6.4%, the feed consumption value was 8.74 g/head/day, the average body weight gain was 0.43 g/head/day, and the average feed conversion was 20.71 g/head. In conclusion as there is no difference between each treatment on cricket performance, the 100% market waste treatment can be used for collared cricket feed.